2020
DOI: 10.1093/nutrit/nuaa039
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation combined with antidepressant drugs for treatment of patients with depression: a systematic review and meta-analysis

Abstract: Context Zinc is an essential trace mineral required for the function of brain and neural structures. The role of zinc supplementation in the prevention and treatment of depression has been suggested in clinical studies that reported a reduction in depressive symptoms. Objective The aim of this review was to determine whether zinc supplementation vs placebo can prevent or improve depressive symptoms in children, adolescents, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Last, legumes are rich in micronutrients, especially zinc, which is another micronutrient related to depression (38,39) . In a recent meta-analysis, zinc supplementation was demonstrated as an effective adjunct therapy to anti-depressant medication (40,41) .…”
Section: Discussionmentioning
confidence: 99%
“…Last, legumes are rich in micronutrients, especially zinc, which is another micronutrient related to depression (38,39) . In a recent meta-analysis, zinc supplementation was demonstrated as an effective adjunct therapy to anti-depressant medication (40,41) .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary zinc supplements have found numerous applications in human health. Being safe, they have been shown to improve neonatal brain development 43 , sleep quality in adults 42 , and to ameliorate health conditions in depression 39 , epilepsy 40 , and a set psychiatric and neurodegenerative states 41 . For example, daily 25mg Zn 2+ applied for 6 weeks in one study 47 , and daily 220mg zinc sulphate (providing 50mg zinc) applied for 12 days in another 48 , was found to positively act on depression patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary zinc supplementation has been applied to treat various human health conditions, including the neurological ones such as depression 39 , epilepsy 40 , psychiatric and neurodegenerative diseases 41 , or sleep disorders 42 , as well as for normal neonatal development 43 . We thus wondered if dietary supplementation of zinc in the Drosophila model of GNAO1 encephalopathy may reveal any bene cial effects.…”
Section: Zpt Restores Cellular Rgs19 Interactions Of Gnao1 Encephalopathy Mutantsmentioning
confidence: 99%
“…The intake led to a reduction in scores related to anger, depression and discouragement along with an increase in serum zinc; these changes were not seen in the placebo group [ 256 ]. Accordingly, the general population with MDD could also obtain advantages, since the research review of patients treated with antidepressants plus supplementation versus placebo concluded that there was better response and recovery for those treated with this trace element [ 257 ]. Selenium is also a vital molecule for our body; the proper dose of it, along with other nutrients, can have a moderate impact on rectifying the development of TDM [ 258 ].…”
Section: Nutritional Intervention In Women With Mddmentioning
confidence: 99%